2018
DOI: 10.3390/app8081396
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Life Cycle Assessment of End-of-Life Silicon Solar Photovoltaic Modules

Abstract: Abstract:The cumulative global photovoltaic (PV) waste reached 250,000 metric tonnes by the end of 2016 and is expected to increase considerably in the future. Hence, adequate end-of-life (EoL) management for PV modules must be developed. Today, most of the EoL modules go to landfill, mainly because recycling processes for PV modules are not yet economically feasible and regulation in most countries is not yet well established. Nevertheless, several methods for recycling PV modules are under development. Life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 23 publications
(53 reference statements)
0
36
0
1
Order By: Relevance
“…Analysis of the FRELP process proved that transport is one of the main aspects responsible for the impacts of PV recycling (Latunussa et al, 2016). Lunardi et al (2018) concluded that transport of PV waste to the recycling facilities should be below 100 km for recycling being environmental convenient compared to other alternatives (e.g. direct incineration or landfilling).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the FRELP process proved that transport is one of the main aspects responsible for the impacts of PV recycling (Latunussa et al, 2016). Lunardi et al (2018) concluded that transport of PV waste to the recycling facilities should be below 100 km for recycling being environmental convenient compared to other alternatives (e.g. direct incineration or landfilling).…”
Section: Resultsmentioning
confidence: 99%
“…In a similar description, Ref. [18] defines LCA as a methodology that quantifies the environmental impacts of a process or a product. In their study, Ref.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…LCA is described as a 'cradle to grave' method for the evaluation of environmental impacts [17]. In a similar description, [18] defines LCA as a methodology that quantifies the environmental impacts of a process or a product. In their study, [19] stated that most of the environmental impacts do not occur in the use, maintenance, and repair of the product but during the manufacturing, transportation, and disposal stages.…”
Section: Appl Sci 2019 9 X For Peer Review 3 Of 13mentioning
confidence: 99%
“…The following authors of the study [5] believe that fluctuations in oil prices lead to an increase in the popularity of energy from renewable sources and may have different effects on exporting and oil-importing countries. The third authors in their works [6,7] focus on certain aspects of energy production, for example, on utilization, and did not consider the whole process of price formation in a complex. It is also worth noting that a lot of information was taken from research and statistical data of such famous international organizations and companies as:…”
Section: The Aim and Objectives Of Researchmentioning
confidence: 99%